(untitled) (Journal of Natural Language and Linguistics, 2025)
This study investigates secondary school Values Education teachers’ attitudes toward using Filipino as a medium of instruction and how these attitudes influence instructional practices and perceived effectiveness. Specifically, the research identifies teacher attitudes, examines instructional practices as a mediator, and assesses instructional outcomes. Using a descriptive-correlational design, validated Likert-scale instruments collected data from 48 licensed Values Education teachers in two public secondary schools in General Santos City. Pearson’s correlation and mediation analyses revealed generally positive teacher attitudes toward Filipino, particularly for enhancing student comprehension and classroom engagement. Instructional practices significantly mediated the relationship between attitudes and perceived instructional effectiveness, suggesting favorable attitudes translated into responsive instructional strategies enhance cognitive and affective learning outcomes. Limitations include the small, localized sample, affecting generalizability. Practical implications emphasize aligning language policies with classroom practices and strengthening teacher training to support effective Filipino use. Future research recommendations include expanding the sample size, exploring broader linguistic contexts, and investigating long-term impacts of language practices on educational outcomes.